Proses Simulasi Sistem Concentrated Solar Power Equipment - Arief Kurnia; Dwi Rahmalina (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa & Inovasi, 2021)
The increase in the use of electrical energy in Indonesia is currently increasing from year to year and the population in Indonesia is increasing very rapidly, therefore we need an energy utilization technology that does not need a lot of money to operate it. Because Indonesia is located on the equator which makes Indonesia has a great potential for sun exposure. Utilization of solar energy can be done by using a technology to generate electricity from solar energy sources, namely Concentrated Solar Power (CSP) technology. Concentrated Solar Power (CSP) is a technology that uses solar energy that produces electrical energy from a component that converts heat energy into electrical energy using a Stirling engine. In this research, the solar energy utilization device developed is a Ground Base type Concentrated Solar Power (CSP) device equipped with a liquid fluid delivery system in the form of a piping system and a Stirling engine. By using a satellite dish measuring 6 feet or 1830 mm, and also added a drive system to move the parabola according to the point of efficient solar heat reception.